Usurpation of Aristocratic Privilege and the Social Identity of the Polish Noble Elite in the Period of the Partitions - Getka-Kenig, Mikołaj (Kwartalnik Historyczny, 2022)
The aristocratic titles, which the partitioning monarchies granted to some of their Polish noble subjects in the long nineteenth century, did not play a decisive role in the development and formation of the modern Polish noble elite. The foreign titles could only sanction the internal noble hierarchy, which was apparently much more determined by specific noble traditions and the cult of the pre-partition past. This argument is evidenced by the cases of families which did not need formal title grants to be recognized as truly aristocratic in that period.